Pandemic Financial Stress in Dental Medicine in Croatia - Edi Orlic; Stjepan Spalj; Natasa Ivancic Jokic; Danko Bakarcic; Odri Cicvaric; Renata Grzic (MDPI AG, 2022)
The aim of this cross-sectional research was to investigate how the COVID-19 pandemic affected the activity of dental medicine in the Republic of Croatia in 2020. It included 136 doctors of dental medicine who completed an online survey regarding their personal and professional information; work in dental offices; and level of fear for their own health, the health of others, and financial existence; and their attitude about vaccination. There was a significantly higher decrease in patient visits in dental offices that do not have a contract with public health insurance (70% vs. 37%; p < 0.001) and in dental offices that have a higher percentage of profit from dental tourism (32% vs. 14%; p < 0.001). Fear of financial existence was significantly higher in the group of dentists who do not have a contract with public health insurance (p = 0.0) and is positively correlated with the percentage of profit from dental tourism (r = 0.299; p < 0.001). Dentists with a higher level of fear that they or their loved ones would get infected due to the nature of their job are more likely to get vaccinated (p ≤ 0.007). The decision to get vaccinated and wearing a disposable coat/apron was related to fear when all other parameters were controlled for (R = 0.44; p = 0.037). In conclusion, the COVID-19 pandemic had a minimal impact on the profession of dental medicine in Croatia but represented a larger financial stress for dentists working in dental offices that do not have a contract with public health insurance and have a higher percentage of income from dental tourism.